The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2014
DOI: 10.1155/2014/405740
|View full text |Cite
|
Sign up to set email alerts
|

Molecular and Morphological Characterization ofFasciolaspp. Isolated from Different Host Species in a Newly Emerging Focus of Human Fascioliasis in Iran

Abstract: The current study aimed to find out the morphometric and genotypic divergences of the flukes isolated from different hosts in a newly emerging focus of human fascioliasis in Iran. Adult Fasciola spp. were collected from 34 cattle, 13 sheep, and 11 goats from Kohgiluyeh and Boyer-Ahmad province, southwest of Iran. Genomic DNA was extracted from the flukes and PCR-RFLP was used to characterize the isolates. The ITS1, ITS2, and mitochondrial genes (mtDNA) of NDI and COI from individual liver flukes were amplified… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
38
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(43 citation statements)
references
References 27 publications
5
38
0
Order By: Relevance
“…The prevalence rate of infection in sheep (17.71%) was higher than the one in cattle (16.71%) and in goats (11.69%)), this study showed high prevalence of Fasciola spp in ruminants, in Dasht Room area (29%), due to high human population and proximity to the city of Yasuj and slaughterhouse is very important [19]. as a result of positive human serum against F. hepatica parasites in the area of Sarkari et al and the contamination of livestock in the study should Dasht Room one of the areas at risk and to prevent the high incidence knew Fasciolosis Awareness of the disease is serious action [20].…”
Section: Resultsmentioning
confidence: 99%
“…The prevalence rate of infection in sheep (17.71%) was higher than the one in cattle (16.71%) and in goats (11.69%)), this study showed high prevalence of Fasciola spp in ruminants, in Dasht Room area (29%), due to high human population and proximity to the city of Yasuj and slaughterhouse is very important [19]. as a result of positive human serum against F. hepatica parasites in the area of Sarkari et al and the contamination of livestock in the study should Dasht Room one of the areas at risk and to prevent the high incidence knew Fasciolosis Awareness of the disease is serious action [20].…”
Section: Resultsmentioning
confidence: 99%
“…Molecular identification of Fasciola species was performed as previously described (Shafiei et al 2014). Briefly, a part of the apical and lateral zone of the adult flukes were removed and homogenized.…”
Section: Dna Extraction and Pcr-rflpmentioning
confidence: 99%
“…Fasciola gigantica is present mainly in tropical and F. hepatica in temperate areas, while both species overlapped in subtropical areas including Egypt and Iran (Soliman 2008;Mas-Coma et al 2009;Moghaddam et al 2004;Shafiei et al 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This province experienced 2 outbreaks of human fascioliasis in 1987 and 1997, affecting more than several thousands of people (3). Moreover, many cases of human fascioliasis were reported from other provinces of Iran (4). Animal fascioliasis is quite frequent in grazing animals generally in most areas of the state and the prevalence reaches about 50% in certain provinces (5).…”
Section: Introductionmentioning
confidence: 99%